Development of Dicot and Monocot Learning Media using Flannel and Cardboard to Improve Biology Learning Outcomes of Junior High School Stundets - Siregar, Rismawati; Anas, Nirwana (Jurnal Pendidikan MIPA, 2022)
Learning media innovation Flanchard, or flannel and cardboard, evolved from bookbased image media into three-dimensional flannel flanchard media.The goal of this study is to create a flanchard-based learning medium that is reliable, useful, and efficient.The research methodology utilized is the research and development (R&D) ADDIE development model, which consists of the following five phases: analysis, design, development, implementation, and evaluation.The 24 students in class VIII at SMP Swasta Bina Siswa served as the study's subjects.Expert and media expert validation sheets for testing feasibility, practitioner validation sheets for testing practicality, pretest and posttest sheets, and student response sheets for testing effectiveness were the instruments used in the research.The study demonstrates that the developed Flanchard-based media is said to be very feasible with a percentage of 84%, very practical with a percentage of 86%, and very effective with an increase in learning in the high category, which was tested with n-gain with a score of 0.7 and participant responses.Keywords: Flanchard, biology learning outcomes, development research. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1308-1319